Associations between interleukin-1 and IL-1 receptor antagonist polymorphisms and susceptibility to rheumatoid arthritis: A meta-analysis - Lee, Y H; Bae, S-C (Cellular and Molecular Biology, 2015)
This study determined whether interleukin-1 (IL-1) polymorphisms are associated with susceptibility to rheumatoid arthritis (RA). A meta-analysis was conducted on the associations between the IL-1A, IL-1B, and IL-1 receptor antagonist (IL-1RN) polymorphisms and RA. A total of 16 studies involving 4,339 RA cases and 3,885 controls were included in the meta-analysis. Meta-analysis of the IL-1B -511 C/T polymorphism revealed an association between the IL-1B -511 T allele and RA in Caucasians (OR = 0.913, 95% CI = 0.840–0.992, p = 0.031), but not in Asians. Ethnicity-specific meta-analysis indicated an association between the TT+TC genotype of the IL-1B 3953 C/T polymorphism and RA in Caucasians (OR = 1.243, 95% CI = 1.008–1.533, p = 0.042) and in Asians (OR = 2.672, 95% CI = 1.662–4.296, p = 4.9x10-6). No association was between RA susceptibility and the IL-1A -889 C/T, IL-1A +4845 G/T, and IL-1RN +2018 C/T polymorphisms. This meta-analysis suggests the IL-1B -511 C/T polymorphism is associated with susceptibility to RA in Caucasians, and that the IL-1B +3953 C/T polymorphism is associated with susceptibility to RA in Caucasians and Asians.